Metastatic phaeochromocytoma in a 23‐year‐old woman with an unclassified variant in the von Hippel Lindau disease gene: how can the pathogenicity of this variant be determined?. (6th February 2015) - Russell, Nicholas; Delatycki, Martin; Grossmann, Mathis
Summary A 23‐year‐old woman with metastatic phaeochromocytoma was found to have a previously unclassified variant in the von Hippel Lindau disease gene (c.361G>C). We use this case to highlight the issue of unclassified single nucleotide variants and the approaches to help predict whether they are disease causing or neutral. With increasing use of genetic testing, and widespread clinical use of next‐generation sequencing around the corner, this issue is likely to become more prominent.